Comparative Analysis of the Concept of Death in Turkish and Japanese Proverbs - Dogan, Guliz (European Scientific Journal, ESJ, 2024)
Death constitutes the last part of the life cycle. Although being born and living are welcomed with joy by human beings, death brings pain and eternal unhappiness. This study aims to reveal how the concept of death, which contains deep sadness, is handled in Turkish and Japanese proverbs. Proverbs are stereotypes passed from one generation to another and are very important in reflecting the lifestyles and ways of thinking of the societies to which they belong. Proverbs are essential in transferring cultural knowledge because our ancestors created them with the accumulation and experience of many years.